2023
DOI: 10.1002/pros.24527
|View full text |Cite
|
Sign up to set email alerts
|

Impact of piflufolastat F‐18 PSMA PET imaging on clinical decision‐making in prostate cancer across disease states: A retrospective review

Abstract: Introduction Piflufolastat F‐18 (18F‐DCFPyL) prostate‐specific membrane antigen (PSMA) positron emission tomography (PET) imaging is approved by the US food and drug administration for initial staging of high‐risk prostate cancer, biochemical recurrence (BCR), and restaging of metastatic prostate cancer. Here, we sought to assess how its integration into clinical care may have impacted the management of patients. Methods We identified 235 consecutive patients who underwent an 18F‐DCFPyL PET scan from August 20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 26 publications
0
1
0
1
Order By: Relevance
“…One study ( 27 ) reported the PET positivity rate of local region, lymph node and metastasis, the number of metastatic detection rate was used. One study ( 28 ) included patients for PS and with BCR, the PET positivity rate was reported separately, and we used the mean value.…”
Section: Methodsmentioning
confidence: 99%
“…One study ( 27 ) reported the PET positivity rate of local region, lymph node and metastasis, the number of metastatic detection rate was used. One study ( 28 ) included patients for PS and with BCR, the PET positivity rate was reported separately, and we used the mean value.…”
Section: Methodsmentioning
confidence: 99%
“…y que la influencia en la estadificación, tratamiento y los resultados de los diagnósticos realizados con las técnicas de imagen de nueva generación más precisas, como el PET colina o el PET PSMA, no está aún esclarecida. La reciente incorporación de estas nuevas pruebas de imagen a la práctica clínica ha impactado de manera significativa tanto en el estadiaje de los pacientes como en su manejo terapéutico posterior, haciendo que en la práctica asistencial deban tomarse decisiones de indicaciones terapéuticas en escenarios no contemplados en los ensayos clínicos pivotales (5)(6)(7).…”
Section: Introductionunclassified